"I didn't say, 'Macbeth, ' it was my Google Doc!": A secondary English case study of redefining learning in the 21st Century. (January 2019) - Marlatt, Rick
The substitution, augmentation, modification, redefinition (SAMR) model offers a framework by which schools and teachers can implement digital tools through curricular design that encourages participatory learning. 21st Century students should be producing content and making meaning in educational settings with high levels of engagement and by the same literacy methods they use in social contexts. This case study examines the digital pedagogy of one English teacher at a Western United States high school. Using the SAMR model as a theoretical framework, this article first reviews relevant literature on creating participatory cultures in schools with Google Docs. Then, through observations, interviews, and artifacts, the analysis attempts to pinpoint specific phases of the teacher's instruction where the potential to enhance academic opportunities is transformed by creativity and collaboration and leads to a redefinition of the learning environment. This article considers both the teacher's pedagogy in her Macbeth unit as well as the school's technology procedures in measuring its progress within the SAMR model.